Azodye ONO Donor Complexes of Co(II), Ni(II) Cu(II), Zn(II) Cd(II) and Hg(II) - Mahapatra, B.B.; Ray, P.; Biswal, B. (Asian Journal of Chemistry, 2010)
Six azodye complexes of composition [MLCl(H2O)2] and [M'LCl] have been prepared where M = Co(II), Ni(II), Cu(II), Zn(II), M' = Cd(II), Hg(II) and LH = 2-(2',4'-dinitro-1-hydroxyphenylazo)- 5-chlorobenwphenone. The complexes of the first category are hexa coordinated having either octahedral or distorted octahedral geometry and the complexes of the latter type are tetracoordinated having tetrahedral stereochemistry based on analytical, conductance, magnetic susceptibility, lR, electronic spectra, ESR, NMR and X-ray diffraction data.